Chronic Kidney Disease: Mineral and Bone Disorder in Children - Wesseling-Perry, Katherine (2013)
Childhood and adolescence are crucial times for the development of a healthy skeletal and cardiovascular system. Disordered mineral and bone metabolism accompany chronic kidney disease (CKD) and present significant obstacles to optimal bone strength, final adult height, and cardiovascular health. Early increases in bone and plasma fibroblast growth factor 23 (FGF23) are associated with early defects in skeletal mineralization. Later in the course of CKD, secondary hyperparathyroidism—due to a combination of declining calcitriol values and phosphate retention—results in high turnover renal osteodystrophy while elevated levels of both phosphate and FGF23 contribute to cardiovascular disease. Treatment of hyperphosphatemia and secondary hyperparathyroidism improves high turnover bone disease but fails to correct defects in skeletal mineralization. Since overtreatment may result in adynamic bone disease, growth failure, hypercalcemia, and progression of cardiovascular calcifications, therapy must therefore be carefully titrated to maintain optimal serum biochemical parameters according to stage of CKD. Newer therapeutic agents and new treatment paradigms may effectively suppress serum PTH levels while limiting intestinal calcium absorption and skeletal FGF23 stimulation and may provide future therapeutic alternatives for children with CKD.